2022
DOI: 10.1111/eip.13325
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relation between psychosis‐like experiences and suicidal ideation, plans, and attempts among college students in the United States

Abstract: Aim The suicide rate among college students is particularly high, with evidence that psychosis‐like experiences (PLEs) put these individuals at greater risk. The current study explored whether there are differential relations between four subtypes of PLEs and three suicide outcomes. Methods We analysed a large sample of college students from the Fall semester cohort of the 2020 Healthy Minds Study (HMS) (weighted N = 36727). PLEs and suicide outcomes were assessed using binary variables from the World Health O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…70 In addition, this study showed consistent mediating effects of insomnia symptoms and resilience in the relationship between DEs/ HEs and SI. Consistent with previous studies, 71 all subtypes of PLEs are positively associated with SI. Studies by Saha et al, 72 and participants were drawn from a large-scale cross-sectional survey, indicating that adolescents with delusional experiences were about two to four times as likely to report SI.…”
supporting
confidence: 92%
“…70 In addition, this study showed consistent mediating effects of insomnia symptoms and resilience in the relationship between DEs/ HEs and SI. Consistent with previous studies, 71 all subtypes of PLEs are positively associated with SI. Studies by Saha et al, 72 and participants were drawn from a large-scale cross-sectional survey, indicating that adolescents with delusional experiences were about two to four times as likely to report SI.…”
supporting
confidence: 92%
“…Given inconsistent findings regarding the relationship between psychosis experiences and suicide thoughts and behaviors, a fine-grained analysis of specific psychosis symptoms (and their severity) with subtypes of suicide thoughts and behaviors (i.e., ideation, plans, attempts, death) could help better understand whether, for example, the association between psychosis and suicide thoughts and behaviors is due to the presence of psychosis symptoms, to specific symptoms (e.g., auditory versus visual hallucinations ( 90 ), to the frequency or intensity of these ( 90 ), to the associated distress ( 91 ), or is mediated by another variable ( 55 ). Relatedly, considerations of unique risk factors and protective factors and sources of strengths for this population should be determined and routinely assessed.…”
Section: Determine the Reliability And Validity Of Suicide Risk Scree...mentioning
confidence: 99%
“…Most people who report PE will not develop a psychotic disorder; however, some studies have shown that PE associate with an increased risk for persistent psychosis (Dominguez et al., 2011 ). Still, a growing and compelling body of literature shows that PE are associated with a host of negative outcomes, including mental health problems (DeVylder et al., 2014 ), chronic health conditions (Oh et al., 2019 ; Oh, Waldman, et al., 2018 ), disability (Navarro‐Mateu et al., 2017 ; Oh, Koyanagi, et al., 2018 ), behavioral problems (Koyanagi et al., 2016 ; Koyanagi & Stickley, 2015 ; Oh, Koyanagi, et al., 2016 ; Oh, Singh, et al., 2016 ), suicidal thoughts and behaviors (DeVylder et al., 2020 ; Jay et al., 2022 ; Oh, Koyanagi, et al., 2022 ; Yates et al., 2019 ), and reduced lifespan (Sharifi et al., 2015 ). As such, PE may play a role in screening, prevention, and early intervention not only for psychotic disorders but also other adverse health outcomes (Oh, DeVylder, et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%